Eficácia da espuma multicamadas de poliuretano com silicone comparada ao filme transparente de poliuretano na prevenção de lesão por pressão: ensaio clínico randomizado autocontrolado (Pressure Injury Prevention Trial – PIPT) - Soares, Rhea Silvia de Avila (2019)
It is relevant to evaluate new technologies in PI prevention to substantiate a professional practice based on scientific evidences. The objective of this research is to evaluate the efficacy of multi-layered soft silicone foam dressing compared to transparent polyurethane film in heels pressure injury prevention, in patients hospitalized in intensive care unit (ICU) with high and very high risk. It was performed a within person randomized clinical trial, developed in a university hospital from south of Brazil, from July 21st 2017 to March 25th 2018. The sample consisted of successive entries of the patients that met the inclusion criteria, from daily visits the ICU for the recruitment of eligible patients, totalling 92 patients and 184 cutaneous sites. Randomization was performed for the heels: intervention group (multi-layered soft silicone foam dressing) and control group (transparent polyurethane film). After randomization and initial data collection (baseline), the intervention was performed according to each group. Data were analyzed by the program Statistical Package for Social Sciences version 21. In order to evaluate the primary outcome (PI development), the incidence and relative risk were calculated. For the variables of the skin microclimate on the first day (baseline) and the last (end), a Wilcoxon test was performed. To analyze the outcome variables between the groups with and without PI development, Student's t test or Mann-Whitney U test was performed. To verify the association between the qualitative independent variables and the development of LP, a Chi- Square or Fisher's exact test was performed. In order to analyze the correlation between the quantitative variables, Spearman's correlation was used. A level of statistical significance of 5% was used. The ethical aspects were observed according to precepts established in Resolution 466/2012 of the National Health Council. The PI incidence was 10.9%, with 8.7% in the intervention group and 13.0% in the control group. The difference in incidence between groups was not significant (p=0.333). The skin temperature of heels that developed LP as well as of heels in use of the transparent polyurethane film did not present significant difference between baseline and end. The factors associated with the PI development were age, length of stay in the study, length of hospital stay prior to ICU, edema and erythema. The study provides additional evidence to support the use of multi-layered soft silicone foam dressing in PI prevention. The relative risk was 0.67, thus those who used multi-layered soft silicone foam dressing had 33% lower risk of PI developing compared to patients using transparent polyurethane film.